FRI0152 On Drug and Drug-Free Remission by Baseline Disease Duration in the Avert Trial: Abatacept Versus Methotrexate Comparison in Patients with Early Rheumatoid Arthritis. (9th June 2015) - Bykerk, V.P.; Burmester, G.R.; Combe, B.G.; Furst, D.E.; Huizinga, T.W.J.; Wong, D.A.; Emery, P.
Abstract : Background: Patients (pts) with RA and longer disease duration generally do not respond as well to treatment with DMARDS as pts with a shorter duration of disease. Earlier use of biologic DMARDs can improve disease control. 1, 2 In the AVERT (A ssessing V ery E arly R heumatoid arthritis T reatment) trial, more pts with early RA achieved DAS28 (CRP) <2.6 after 12 mths of treatment with SC abatacept (ABA)+MTX as well as 6 mths after rapid withdrawal of all RA therapy, compared with MTX alone. 3 The AVERT trial provides the opportunity to examine outcomes in pts with varying degrees of early disease duration where the definition for disease duration is well defined across groups. Objectives: To assess clinical outcomes in pts with early RA and ≤3 mths disease duration compared with pts with >3 to ≤6 or >6 mths disease duration after treatment with SC ABA+MTX or MTX alone, using data from AVERT. Methods: Pts with early active RA (clinical synovitis in ≥2 joints for ≥8 wks, persistent symptoms for ≤2 yrs and DAS28 [CRP] ≥3.2), and who were anti-cyclic citrullinated peptide-2 positive, were randomized to SC ABA 125 mg/wk + MTX, SC ABA 125 mg/wk alone or MTX alone for 12 mths. All RA treatment was removed after 12 mths in pts with DAS28 (CRP) <3.2. 3 In this post hoc analysis, the proportions of pts achieving protocol-defined remission (DAS28 [CRP] <2.6) or improvement in physical function (HAQ-DI; ≥0.3 units from baseline [BL]) were assessed by disease duration (defined as the duration of persistent symptoms at BL) and treatment group. Adjusted mean changes from BL in HAQ-DI were also evaluated by disease duration. Results: Pts were randomized and treated with ABA+MTX (n=119) or MTX (n=116): 36 pts on ABA+MTX and 48 on MTX with ≤3 mths disease duration; 34 pts on ABA+MTX and 29 on MTX with >3 to ≤6 mths disease duration; 49 pts on ABA+MTX and 39 on MTX with >6 mths disease duration. No systematic differences were seen in BL demographics and clinical characteristics when pts were grouped by disease duration. Irrespective of BL disease duration, a higher proportion of ABA+MTX-treated pts achieved DAS-defined remission at Mth 12, and sustained remission at Mth 18, compared with MTX alone. The largest treatment difference in sustained remission following all treatment withdrawal (measured at 12–18 mths) was observed in pts with ≤3 mths disease duration. In the ABA+MTX group, a higher proportion of pts with disease duration ≤3 mths (33%) maintained DAS-defined remission compared with pts with longer disease durations (>3 to ≤6 mths, 14.7%; >6 mths, 10.2%) (Figure ). The ABA+MTX group with ≤3 mths disease duration also had the fastest onset of response (Figure ). Results for HAQ-DI response were similar to the overall population results, regardless of BL disease duration. Conclusions: Disease duration of ≤3 mths was predictive of faster onset of clinical response and the ability to achieve higher rates of drug-free remission following treatment with abatacept +MTX in AVERT. References: Westhovens R et al. Ann Rheum Dis 2009;68:1870–7. Emery P et al. Ann Rheum Dis 2010;69:510–6. Emery P et al. Ann Rheum Dis 2014;73(Suppl 2): 69 Disclosure of Interest: V. P. Bykerk Grant/research support from: Amgen, Pfizer, Bristol-Myers Squibb, Janssen, UCB, Roche/Genentech, Consultant for: Amgen, Pfizer, Bristol-Myers Squibb, UCB, Roche, G. R. Burmester Grant/research support from: Bristol-Myers Squibb, AbbVie, Pfizer, Medimmune, Novartis, Roche, UCB, Lilly, Consultant for: Bristol-Myers Squibb, AbbVie, Pfizer, MSD, Medimmune, Roche, UCB, Speakers bureau: Bristol-Myers Squibb, AbbVie, Pfizer, MSD, Roche, UCB, B. G. Combe Grant/research support from: Pfizer, Roche-Chugai, Speakers bureau: Bristol-Myers Squibb, Merck, Pfizer, Roche-Chugai, UCB, D. E. Furst Grant/research support from: AbbVie, Actelion, Amgen, Bristol-Myers Squibb, Gilead, GSK, NIH, Novartis, Pfizer, Roche/Genentech, UCB, Consultant for: AbbVie, Actelion, Amgen, Bristol-Myers Squibb, Cytori, Janssen, Gilead, GSK, NIH, Novartis, Pfizer, Roche/Genentech, UCB, T. W. J. Huizinga Grant/research support from: EU & Dutch Arthritis Foundation, Consultant for: Abbott Laboratories, Biotest AG, Bristol-Myers Squibb, Crescendo Bioscience, Inc, Novartis Pharmaceuticals Corporation, Pfizer Inc, Roche, sanofi-aventis, Schering-Plough, UCB, Inc., Eli Lilly, Meteor Board, D. A. Wong Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, P. Emery Grant/research support from: AbbVie, Merck, Pfizer, Roche, Consultant for: AbbVie, Bristol-Myers Squibb, Merck, Pfizer, Roche, Lilly, Novartis